Psychometric properties and factorial exploration of the Mexican version of the Parental-Caregivers Perceptions Questionnaire - Romo Pérez, Camilo (2022)
Objective: To evaluate the psychometric properties of the Mexican version of the Parental-Caregivers Perceptions Questionnaire. Materials and methods: A psychometric scale validation study developed in Poza Rica (Veracruz-México) that cross-culturally adapted the Parental-Caregivers Perceptions Questionnaire from Peruvian Spanish to Mexican slang. Face validity was evaluated through the judgment of experts who rated the clarity, relevance and importance of the questions. The sample was 241 parents and caregivers. Reliability was assessed using Cronbach's alpha and McDonald's Omega, internal consistency, and discriminant power using Spearman's correlation coefficient, and content validity was assessed using Exploratory Factor Analysis. Results: The scale showed an α=0.81 and ω=0.8. The matrix tests presented a Kaiser-Meyer-Olkin index=0.739 (p=0.001); Bartlett's test (p=0.001). Various solutions were explored and a four-factor model capable of explaining 52.3% of the accumulated variance was considered the benchmark, in which 11 items were extracted from the original scale with loads <0.4. Conclusions: The Mexican version of the Parental-Caregivers Perceptions Questionnaire presented an optimal response to reproducibility and good content validity. The revision of the eliminated items and the confirmatory factor analysis are suggested to admit a definitive version of the scale.